Sintered body

JP2025021855APending Publication Date: 2025-02-14PROTERIAL LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023125866
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0021】 この発明によれば、MIMを適用した簡易な手段で量産可能な、加熱焼結時の歪な収縮や歪な変形が小さく抑制された焼結体(焼結変形が抑制された焼結体)を提供することができる。また、この発明に係る焼結変形が抑制された焼結体は、本焼結やHIP処理の後に行われている形状矯正や仕上加工の削減や低減を可能にするため、焼結体の生産効率の向上に貢献することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021855000001_ABST
    Figure 2025021855000001_ABST
Patent Text Reader

Abstract

To provide a sintered body (sintered body in which sintering deformation is suppressed) that enables mass production by simple means to which MIM is applied, and in which distorted contraction and distorted deformation at the time of heating and sintering are suppressed.SOLUTION: A sintered body has a cumulative frequency distribution curve of a crystal particle size satisfying d80 / (d90-d10)≤1.20 and d70 / (d90-d10)≤1.03. When an organic component is removed from a molded body obtained by injection molding a kneaded product containing mixed metal powder and the organic component, and metal powder is heated and sintered, when median diameters of a cumulative frequency distribution curve of standard metal powder, first metal powder and second metal powder are represented by d50A, d50P and d50Q, the sintered body can be manufactured by a method for manufacturing mixed metal powder in a mixed ratio of first metal powder of 20 vol.% to 80 vol.% using the first metal powder having d50P / d50A of 2 to 5 and second metal powder having d50Q / d50A of 0.1 to 0.8, and manufacturing a kneaded product in a mixed ratio of the mixed metal powder of 60 vol.% to 80 vol.%.SELECTED DRAWING: Figure 8
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sintered body, and more particularly to a sintered body in which sintering deformation is suppressed, which is produced by applying a metal powder injection molding method using a kneaded product containing a metal powder and an organic component. [Background technology]

[0002] Conventionally, metal injection molding (MIM) is known as one of the methods for manufacturing sintered bodies. MIM is applied in many industrial fields because it can mass-produce relatively small sintered bodies or sintered bodies with complex and fine shapes in a shape close to the final product (near net shape). A typical MIM process includes a kneaded product preparation process for preparing a kneaded product (compound) containing metal powder and organic components, a compact preparation process for preparing a compact (green body) by injection molding the kneaded product, a degreased body preparation process for removing the organic components constituting the compact to prepare a degreased body (brown body), and a sintered body preparation process for sintering the metal powder constituting the degreased body by heating to prepare a sintered body. In addition, if necessary, a calcined body preparation process is included in which the metal powder constituting the degreased body is sintered to a degree that allows handling to prepare a calcined body, and a sintered body preparation process is adopted in which the metal powder constituting the calcined body is sintered more firmly to prepare a sintered body instead of the degreased body.

[0003] For example, Patent Document 1 discloses a method for producing a sintered body using MIM, in which a kneaded material containing metal powder and a binder is injection molded to produce a molded body, the binder constituting the molded body is removed by heating to produce a degreased body, and the degreased body is sintered by heating to produce a sintered body. In the method for producing a sintered body disclosed in Patent Document 1, the ratio (mixing ratio) of metal powder in the kneaded material is set to about 60% by volume, thereby suppressing deformation of the degreased body. Then, the metal powder constituting the degreased body is heated and sintered to produce a sintered body. However, Patent Document 1 does not disclose any specific means for suppressing the distortion shrinkage and distortion of the sintered body that are likely to occur during heating and sintering.

[0004] Regarding the suppression of the distorted shrinkage and distortion that are likely to occur in the sintered body during the heating and sintering, for example, Patent Document 2 discloses a method for producing a sintered body, which includes a first kneaded product preparation step of preparing a first kneaded product containing a first metal powder and a binder, a granulated powder preparation step of granulating the first kneaded product to prepare a relatively large-diameter granulated powder, and a second kneaded product preparation step of preparing a second kneaded product containing the granulated powder, a second metal particle, and a binder, and injection molding the second kneaded product to produce a sintered body. In this method for producing a sintered body, a second kneaded product is prepared in which the second metal powder and the binder are arranged in a balanced manner so as to surround the granulated powder that constitutes the skeleton. It is said that by using the second kneaded product, the shape retention of the molded body is improved, making it possible to produce a homogeneous molded body with little deformation, and ultimately making it possible to produce a sintered body with high dimensional accuracy. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2001-152205 A [Patent Document 2] JP 2018-145481 A [Non-patent literature]

[0006] [Non-Patent Document 1] Hideshi Miura, Takeshi Masuda, Tadashi Ogasawara, and Yoshimitsu Samukawa, co-authors, Improvement of performance of Ti injection molded bodies, Powder and Powder Metallurgy Journal, Vol. 49, No. 9, 2002, p. 825-828 [Non-Patent Document 2] Hideshi Miura, Mitsuya Takemasu, Yuki Kuwano, Yoshinori Ito, and Kenji Sato, Sintering Behavior and Mechanical Properties of Ti-6Al-4V Injection Molded Materials, Powder and Powder Metallurgy Journal, Vol. 53, No. 10, 2006, pp. 815-820 Summary of the Invention [Problem to be solved by the invention]

[0007] If the amount of deformation of the sintered body becomes excessive due to the distortion shrinkage or distortion deformation during heating and sintering, it may become necessary to perform excessive machining processes such as correcting or removing the deformed parts of the sintered body. In that case, the near-net-shape effect of the sintered body by MIM is invalidated, and the increase in the number of machining processes may cause problems inconvenient for mass production of sintered bodies, such as an increase in lead time and an increase in manufacturing costs. However, in the manufacturing method of a sintered body disclosed in Patent Document 2, in addition to the above-mentioned processes performed in general MIM, at least a granulated powder manufacturing process and a second kneaded material manufacturing process are performed. Therefore, compared to the mass production of sintered bodies by general MIM, the above-mentioned problems inconvenient for mass production of sintered bodies due to the increase in the above-mentioned processes are concerned. In addition, in this manufacturing method of a sintered body, there is a concern that the granulated powder will be damaged when the second kneaded material is produced. As a countermeasure against the damage of the granulated powder, Patent Document 2 teaches increasing the geometric isotropy of the granulated powder and optimizing the balance between the granulated powder and the first metal powder. Specifically, it teaches how to prepare granulated powder having a predetermined aspect ratio, and how to prepare granulated powder having a predetermined particle size ratio with respect to the first metal powder. With regard to the preparation of such specific granulated powder, the above-mentioned disadvantageous problems are also feared in mass production of sintered bodies.

[0008] An object of the present invention is to provide a sintered body in which distortion shrinkage and distortion during heating and sintering are kept small (sintered body in which sintering distortion is suppressed), which can be mass-produced by a simple means using MIM. [Means for solving the problem]

[0009] The inventors have investigated the configurations of metal powder, organic components, kneaded materials, green bodies, degreased bodies, calcined bodies, and sintered bodies in conventional manufacturing methods for sintered bodies using MIM, as well as their behavior during manufacturing, particularly during heating and sintering, from various perspectives, and have found that a sintered body in which the crystal grains that make up the sintered structure have a specific grain size balance has a smaller deformation ratio of the sintering deformation amount compared to a conventional sintered body.The inventors then thoroughly examined and investigated in detail the differences between conventional sintered bodies and sintered bodies with a smaller deformation ratio of the sintering deformation amount, and found that the above-mentioned problems could be solved by specific ingenuity, which led to the invention.

[0010] That is, in the sintered body with suppressed sintering deformation according to the present invention, when the 10% crystal grain size in the cumulative frequency distribution curve of the crystal grain size is d10, the 70% crystal grain size is d70, the 80% crystal grain size is d80, and the 90% crystal grain size is d90, the cumulative frequency distribution curve satisfies d80 / (d90-d10)≦1.20 and d70 / (d90-d10)≦1.03. The sintered body having this structure is highly likely to have a deformation ratio of 0.8 or less in the amount of sintering deformation during heating and sintering.

[0011] In addition, in the sintered body with suppressed sintering deformation according to the present invention, when the crystal grain size at 60% frequency in the cumulative frequency distribution curve is defined as d60, the cumulative frequency distribution curve satisfies (d90-d70) / (d90-d10)≧0.35. The sintered body having this configuration is highly likely to have a deformation ratio of 0.8 or less in the amount of sintering deformation during heating and sintering.

[0012] In addition, the sintered body of the present invention, in which sintering deformation is suppressed, preferably has the cumulative frequency distribution curve satisfying d80 / (d90-d10)≦1.16 and d70 / (d90-d10)≦0.99. The sintered body having this configuration is highly likely to have a deformation ratio of 0.5 or less of the sintering deformation amount during heating and sintering.

[0013] In addition, the sintered body of the present invention in which sintering deformation is suppressed preferably has an integrated frequency distribution curve that satisfies (d90-d70) / (d90-d10) ≧ 0.39. The sintered body having this configuration is highly likely to have a deformation ratio of 0.5 or less of the sintering deformation amount during heating and sintering.

[0014] In addition, the sintered body of the present invention, which is suppressed in sintering deformation, may be made of an α+β titanium alloy. The sintered body of the present invention also has a preferable effect when made of an α+β titanium alloy.

[0015] The sintered body according to the present invention, in which the above-mentioned sintering deformation is suppressed, can be mass-produced by a simple means using MIM, for example, by the following manufacturing method.

[0016] The above-mentioned sintered body in which sintering deformation is suppressed includes, for example, a kneaded product preparation step of preparing a kneaded product containing a mixed metal powder and an organic component, a molded body preparation step of injection molding the kneaded product to prepare a molded body, a degreased body preparation step of removing the organic component constituting the molded body to prepare a degreased body, and a sintered body preparation step of sintering the metal powder constituting the degreased body by a first heating to prepare a sintered body, and in the kneaded product preparation step, The mixed metal powder can be produced by the following production method: using a first metal powder having a d50P / d50A ratio of 2 to 5 and a second metal powder having a d50Q / d50A ratio of 0.1 to 0.8, the mixed metal powder is produced so that the mixing ratio of the first metal powder is 20% by volume or more and 80% by volume or less, and the kneaded product is produced so that the mixing ratio of the mixed metal powder is 60% by volume or more and 80% by volume or less, where d50A, d50P, and d50Q are particle sizes (median diameters) corresponding to 50 volume% of the calculated volume distribution curve.

[0017] In the above-mentioned method for producing a sintered body, preferably, in the kneaded product preparation step, the mixed powder is prepared so as to have an integrated volume distribution curve showing two peaks, and the difference in particle size corresponding to the distance between the two peaks is 30 μm or more and 70 μm or less.

[0018] In the above-mentioned method for producing a sintered body, preferably, in the kneaded product preparation step, the mixed powder is prepared having an integrated volume distribution curve showing two peaks, and the difference in integrated volume corresponding to the depth of the valley between the two peaks is 2% or more and 10% or less.

[0019] The above-mentioned method for producing a sintered body preferably includes a calcined body production step of sintering the metal powder constituting the degreased body by a second heating at a lower temperature than the first heating to produce a calcined body, and in the sintered body production step, the calcined body is used in place of the degreased body.

[0020] In the above-mentioned method for producing a sintered body, the first metal powder and the second metal powder are made of an α+β titanium alloy. The method for producing a sintered body according to the present invention also has favorable effects when the first metal powder and the second metal powder are made of an α+β titanium alloy. Effect of the Invention

[0021] According to the present invention, it is possible to provide a sintered body in which distortion shrinkage and distortion deformation during heating and sintering are suppressed to a small extent (sintered body in which sintering deformation is suppressed), which can be mass-produced by a simple means using MIM. In addition, the sintered body in which sintering deformation is suppressed according to the present invention makes it possible to reduce or eliminate shape correction and finishing processes that are performed after the main sintering and HIP treatment, and therefore contributes to improving the production efficiency of sintered bodies. [Brief description of the drawings]

[0022] [Figure 1] 1 is a graph showing an accumulated volume distribution curve of Powder A, which is an example of a standard metal powder. [Diagram 2] 1 is a cumulative volume distribution curve (graph) of a powder S1 which is an example of a first metal powder. [Diagram 3] 1 is a cumulative volume distribution curve (graph) of powder S2, which is an example of a second metal powder. [Figure 4] 1 is a cumulative volume distribution curve (graph) of Powder B, which is an example of the mixed metal powder. [Diagram 5] 1 is a cumulative volume distribution curve (graph) of Powder C, which is an example of the mixed metal powder. [Figure 6] 1 is a graph showing the deformation ratios of the sintering deformation amounts of the sintered bodies of Experiment Nos. 1 to 9, with the mixing ratio (volume %) of the powder in the kneaded products of Experiment Nos. 1 to 9 on the horizontal axis. [Figure 7] 1 shows representative cross-sectional photographs of sintered bodies A to C. [Figure 8] The graph shows experimental values ​​d10 / d10 to d90 / d10 shown in Table 4, with the cumulative frequency of the number of crystal grains in the sintered body plotted on the horizontal axis. [Figure 9] The expected value of the deformation ratio of the sintering deformation amount of the sintered body is plotted on the horizontal axis, and d40 / (d90-d10) to d80 / (d90-d10) shown in Table 6 as estimated values ​​are graphed. [Figure 10] The expected value of the deformation ratio of the sintering deformation amount of the sintered body is plotted on the horizontal axis, and the estimated values ​​(d90-d40) / (d90-d10) to (d90-d80) / (d90-d10) shown in Table 6 are plotted on the horizontal axis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, an embodiment of a sintered body (hereinafter simply referred to as "sintered body") with suppressed sintering deformation according to the present invention and an embodiment of a method for manufacturing the sintered body will be described with reference to the drawings as appropriate. The sintered body according to the present invention and the method for manufacturing the sintered body are not limited to the contents of the embodiments exemplified here. The sintered body according to the present invention is defined by the claims, and includes all modifications within the meaning and scope equivalent to the claims. In addition, in the sintered body according to the present invention, the grain size of the crystal grains constituting the sintered structure of the sintered body is represented by the diameter (circle equivalent diameter) of a circle having an area corresponding to the cross-sectional area of ​​the crystal grain. In addition, in the sintered body according to the present invention, the grain sizes corresponding to 10% frequency, 20% frequency, ..., 80% frequency, and 90% frequency of the cumulative frequency distribution curve (hereinafter referred to as "frequency distribution") of the grain size (circle equivalent diameter) constituting the sintered structure of the sintered body and its number are represented in the above order as d10, d20, ..., d80, and d90. In addition, in the manufacturing method for producing a sintered body according to the present invention, the particle sizes of the metal powder (particles) constituting the sintered structure of the sintered body and the particle sizes corresponding to 10 volume %, 50 volume %, and 90 volume % of the integrated volume distribution curve (hereinafter referred to as "volume distribution") relating to the particle size and the volume of the metal powder (particles) constituting the sintered structure of the sintered body are expressed as d10, d50, and d90, as above.

[0024] The sintered body according to the present invention has a cumulative frequency distribution curve (frequency distribution) of crystal grain size that satisfies d80 / (d90-d10)≦1.20 and d70 / (d90-d10)≦1.03. The sintered body having this configuration is highly likely to have a deformation ratio of 0.8 or less in sintering deformation amount during heating and sintering. The deformation ratio of sintering deformation amount during heating and sintering will be described later.

[0025] In addition, the sintered body according to the present invention has a cumulative frequency distribution curve (frequency distribution) of the crystal grain size that satisfies (d90-d70) / (d90-d10) ≧ 0.35. The sintered body having this configuration is highly likely to have a deformation ratio of the sintering deformation amount during heating and sintering of 0.8 or less, similar to the sintered body having the frequency distribution of the crystal grain size that satisfies d80 / (d90-d10) ≦ 1.20 and d70 / (d90-d10) ≦ 1.03.

[0026] The sintered body having a deformation ratio of 0.8 or less during sintering can be said to be a sintered body with suppressed deformation due to shrinkage and deformation during sintering. It has been confirmed by experiments that the deformation ratio of the sintered deformation of a sintered body having a frequency distribution of crystal grain size that satisfies d80 / (d90-d10)≦1.20 and d70 / (d90-d10)≦1.03 is highly likely to be 0.8 or less, and that the deformation ratio of the sintered deformation of a sintered body having a frequency distribution of crystal grain size that satisfies (d90-d70) / (d90-d10)≧0.35 is highly likely to be 0.8 or less, as will be described later.

[0027] The sintered body according to the present invention preferably has a cumulative frequency distribution curve (frequency distribution) of crystal grain size that satisfies d80 / (d90-d10)≦1.16 and d70 / (d90-d10)≦0.99. The sintered body having this configuration is highly likely to have a deformation ratio of 0.5 or less in the amount of sintering deformation during heating and sintering.

[0028] In addition, the sintered body according to the present invention preferably has a cumulative frequency distribution curve (frequency distribution) of the crystal grain size satisfying (d90-d70) / (d90-d10) ≧ 0.35. The sintered body having this configuration is highly likely to have a deformation ratio of the sintering deformation amount during heating and sintering of 0.5 or less, similar to the sintered body having the frequency distribution of the crystal grain size satisfying d80 / (d90-d10) ≦ 1.16 and d70 / (d90-d10) ≦ 0.99.

[0029] The sintered body having a deformation ratio of 0.5 or less during sintering can be said to be a sintered body with suppressed deformation due to sintering, in which the shrinkage and deformation during sintering are sufficiently suppressed. It has been confirmed by experiments that the deformation ratio of the sintered deformation of a sintered body having a crystal grain size frequency distribution satisfying d80 / (d90-d10)≦1.16 and d70 / (d90-d10)≦0.99 is highly likely to be 0.5 or less, and that the deformation ratio of the sintered deformation of a sintered body having a crystal grain size frequency distribution satisfying (d90-d70) / (d90-d10)≧0.35 is highly likely to be 0.5 or less, as will be described later.

[0030] As described above, if the amount of sintering deformation of the sintered body becomes excessive due to the distortion shrinkage or distortion deformation during heating and sintering, it becomes necessary to perform excessive mechanical processing such as correction or removal of the deformed parts of the sintered body, which may cause problems in mass production of sintered bodies such as an increase in lead time and an increase in manufacturing costs. However, if the deformation ratio of the sintering deformation amount during heating and sintering is suppressed to a small value, the sintered body will not have excessively deformed parts due to the near net shape effect of MIM. The smaller the deformation ratio of the sintering deformation amount of the sintered body, the better, preferably 0.8 or less, more preferably 0.7 or less or 0.6 or less, and even more preferably 0.5 or less. If the deformation ratio of the sintering deformation amount of the sintered body is suppressed to a small value as described above, excessive mechanical processing such as correction or removal of the deformed parts is not required in mass production. Therefore, the decrease in the material yield of the sintered body and the increase in the processing man-hours are suppressed, which can contribute to improving the production efficiency of the sintered body.

[0031] The sintered body according to the present invention may be a sintered body made of an α+β titanium alloy. When the crystal grain size of the sintered body made of an α+β titanium alloy shows a frequency distribution that satisfies the above-mentioned specific relationship, the deformation ratio of the sintering deformation amount is highly likely to be 0.8 or less (preferably 0.5 or less). In that case, the sintered body made of the α+β titanium alloy may be said to be a deformation-suppressed sintered body that has small distortion shrinkage and distortion during heating and sintering.

[0032] The above-mentioned sintered body according to the present invention can be mass-produced by a simple means using MIM, for example, a manufacturing method including the following steps (1) to (4), and, if necessary, including the following step (5) before the following step (4).

[0033] (1) A process for preparing a mixed metal powder and preparing a mixed material containing the mixed metal powder and an organic component. (2) A process for producing a molded body by injection molding the kneaded material. (3) A degreased body preparation process for removing the organic components constituting the compact to prepare a degreased body. (4) A sintered body preparation step in which the metal powder constituting the degreased body is sintered by a first heating to prepare a sintered body. (5) A calcination process in which the metal powder constituting the degreased body is sintered by a second heating process at a lower temperature than the first heating process to produce a calcined body.

[0034] The above steps (1) to (3), (5) and (4) will be described below in that order. Note that the manufacturing method of the sintered body according to the present invention is not limited to the manufacturing method of the sintered body that performs the above step (5). In addition, when manufacturing the sintered body in the above step (4), even if the sintered body has a small sintering deformation, a step of removing distortion or straightening, a step of performing mechanical processing such as cutting, grinding and polishing, a step of performing heat treatment such as HIP (Hot Isostatic Pressing) treatment, or a step of performing surface treatment such as cleaning and plating treatment may be performed according to the specifications such as the dimensional accuracy and various characteristics.

[0035] <Mixed material preparation process> In the kneaded product preparation step, first, a mixed metal powder is prepared, and a kneaded product containing the mixed metal powder and an organic component is prepared. A standard metal powder, a first metal powder, and a second metal powder are used to prepare the mixed metal powder. The mixed metal powder is prepared so that the mixing ratio of the first metal powder is 20 volume % or more and 80 volume % or less. In this case, when the particle size (median size) corresponding to 50 volume % in the volume distribution of each of the standard metal powder, the first metal powder, and the second metal powder is d50A, d50P, and d50Q, respectively, a first metal powder having a d50P / d50A of 2 or more and 5 or less, and a second metal powder having a d50Q / d50A of 0.1 or more and 0.8 or less are used. By using the first metal powder and the second metal powder having this configuration, a mixed metal powder showing a volume distribution having a specific form described later can be prepared. The volume distribution of the metal powders was measured using a particle size distribution measuring device MT3000II from Microtrack Bell Corporation (measurement range: 0.02 μm to 2.8 mm, measurement principle: laser diffraction and scattering, laser: three red lasers (wavelength 780 nm)).

[0036] Here, the above-mentioned "standard metal powder" refers to a metal powder that is generally used in MIM. Standard metal powders can be selected by referring to the contents of research papers and magazines (powder and powder metallurgy, etc.) and the original public data of MIM manufacturers and research institutes. Standard metal powders vary depending on the material, but for example, in the case of high-purity titanium (pure Ti) powder, gas-atomized Ti powder with a particle size of 45 μm or less, which is considered to be the median diameter, is used (see Non-Patent Document 1). For example, in the case of 64 titanium, which will be described later, gas-atomized Ti-6Al-4V alloy powder with a particle size of 45 μm or less, which is considered to be the median diameter, is used (see Non-Patent Document 2).

[0037] An example of the volume distribution of the standard metal powder, the first metal powder, and the second metal powder is shown in FIG. 1, FIG. 2, and FIG. 3. FIG. 1 is an example of the volume distribution of the standard metal powder (hereinafter referred to as "Powder A"). FIG. 2 is an example of the volume distribution of the first metal powder (hereinafter referred to as "Powder S1"). FIG. 3 is an example of the volume distribution of the second metal powder (hereinafter referred to as "Powder S2"). Powder A, Powder S1, and Powder S2 all show a particle size distribution with one peak and have the characteristics shown in Table 1. In this example, the d50 (d50A) of Powder A, which is the standard metal powder, is 25.4 μm, the d50 (d50P) of Powder S1, which is the first metal powder, is 63.7 μm, and the d50 (d50Q) of Powder S2, which is the second metal powder, is 19.9 μm. In addition, the d50P / d50A of the powder S1, which is the first metal powder, is 2.5, and the d50Q / d50A of the powder S2, which is the second metal powder, is 0.8.

[0038] [Table 1]

[0039] An example of the particle size distribution of the mixed metal powder using the above-mentioned powders S1 and S2 is shown in Fig. 4 and Fig. 5. Fig. 4 is an example of the particle size distribution of the mixed metal powder shown as powder B in Table 2. Fig. 5 is an example of the particle size distribution of the mixed metal powder shown as powder C in Table 2. The mixed metal powders, powders B and C, have a mixing ratio of the first metal powder, powder S1, in the range of 20 volume % or more and 80 volume % or less. Specifically, the mixing ratio of powder S1 in powder B is 30 volume %, and the mixing ratio of powder S1 in powder C is 50 volume %.

[0040] [Table 2]

[0041] The mixed metal powder produced by mixing the first metal powder and the second metal powder having the above-mentioned configuration within the above-mentioned mixing ratio range shows a volume distribution with a specific form. Specifically, the mixed metal powder has two peaks. The particle size difference corresponding to the interval between the two peaks of the mixed metal powder (particle size difference between the peaks) is within the range of 30 μm to 70 μm, preferably 40 μm to 60 μm, from the viewpoint of suppressing deformation of the sintered body. As shown in Table 2, the particle size difference between peaks 1 and 2 (see Pw shown in the figure) is 32.4 μm in the case of Powder B exemplified above, and 40.1 μm in the case of Powder C.

[0042] In addition, the difference in the cumulative volume (volume %) corresponding to the depth of the valley between the two peaks of the mixed metal powder is set to a range of 2% to 10% in terms of suppressing the deformation of the sintered body. If the purpose is to suppress the deformation of the sintered body as small as possible, it is preferably set to a range of 2% to 4% and more preferably to a range of 2% to 3.5%. If the purpose is to further stabilize the suppression effect of the sintered body, it is preferably set to a range of 4% to 10% and more preferably to a range of 5% to 9%, and in either case, the upper limit can be set to 8% or less. The depth of the valley between the peaks is the difference (volume %) between the maximum and minimum values ​​of the cumulative volume obtained between the two peaks. As shown in Table 2, the depth of the valley between peaks 1 and 2 (see Pv shown in the figure) is 4.3% in the case of powder B exemplified above, and 2.7% in the case of powder C.

[0043] The use of a mixed metal powder showing a volume distribution with the above-mentioned specific morphology helps to obtain the effect of suppressing the distorted shrinkage and distortion of the sintered body. When a mixed metal powder showing a volume distribution with the above-mentioned specific morphology is used, it is considered that in the process in which the mixed metal powder is sintered and changes into crystal grains that constitute the sintered structure, the grain size balance of the crystal grains becomes a state in which strong anisotropic shrinkage is unlikely to occur, thereby suppressing the distorted shrinkage and distortion of the sintered body. At present, it is technically difficult to dynamically observe the transition from metal powder to crystal grains that constitute the sintered structure during sintering and the change in the grain size balance of the crystal grains.

[0044] After preparing the mixed metal powder as described above, a kneaded product containing the mixed metal powder and an organic component is prepared. At this time, the kneaded product is prepared so that the mixing ratio of the mixed metal powder in the kneaded product is 60% by volume or more and 80% by volume or less. From the viewpoint of improving the fluidity and filling property of the kneaded product, the mixing ratio of the mixed metal powder in the kneaded product is preferably 64% to 76%. When a kneaded product having a mixing ratio of the mixed metal powder of less than 60% by volume is used, the voids inside the degreased body (or the calcined body) increase accordingly, so that even if a mixed metal powder showing a particle size distribution with the above-mentioned specific form is used, the distorted shrinkage and distorted deformation of the sintered body may not be sufficiently suppressed. In addition, when a kneaded product having a mixing ratio of the mixed metal powder of more than 80% by volume is used, the voids inside the degreased body (or the calcined body) are reduced accordingly, which is advantageous for suppressing the distorted shrinkage and distorted deformation of the sintered body. However, a kneaded material with a mixed metal powder ratio of more than 80 volume % lacks fluidity and filling properties, so injection molding of a compact using the kneaded material may be difficult.

[0045] The first metal powder and the second metal powder used in the mixed metal powder described above may be metal powders manufactured by any method, such as atomization methods such as water atomization, gas atomization, and high-speed rotating water flow atomization, reduction, carbonyl, and pulverization, as long as the first metal powder has a d50P / d50A of 2 or more and 5 or less, and the second metal powder has a d50Q / d50A of 0.1 or more and 0.8 or less. Metal powders manufactured by atomization are preferable, and metal powders manufactured by gas atomization in particular have individual particles with a nearly spherical shape, which can improve the fluidity and filling properties of the mixed metal powder and the kneaded product using the same.

[0046] The first metal powder and the second metal powder can be selected according to the application and the desired characteristics. The first metal powder and the second metal powder may be metal powders made of metal materials consisting of one or more of elements such as Fe, Ni, Co, Cr, Mn, Zn, Pt, Au, Ag, Cu, Pd, Al, W, Ti, Ta, V, Mo, Nb, Zr, Pr, Nd, and Sm. The metal materials are not limited to high-purity metal materials (pure metals), and may be alloy materials such as Fe-based alloys such as stainless steel, low-carbon steel, and low-thermal expansion alloys, Ni-based alloys such as Alloy 713C, Alloy 713LC, and Alloy 718, and Ti-based alloys such as Ti-6%Al-4%V (mass%) and Ti-3%Al-2.5%V (mass%).

[0047] Here, an α+β titanium alloy is taken as an example. The α+β titanium alloy is a Ti-based alloy that is composed of Ti as a base and selectively added with elements such as Al, V, Mn, Fe, Zr, Mo and Sn. The above-mentioned elements such as Al, V and Sn are selectively added in the range of, for example, Al 8% by mass or less, V 10% by mass or less, Mn 8% by mass or less, Fe 2% by mass or less, Zr 4% by mass or less, Mo 6% by mass or less, and Sn 2.5% by mass or less relative to Ti. Specifically, for example, in addition to the well-known Ti-6%Al-4%V (mass%) called 64 titanium, Ti-3%Al-2.5%V (mass%), Ti-6%Al-4%V-2%Sn (mass%) and Ti-6%Al-6%V-2%Sn (mass%) are known as α+β titanium alloys.

[0048] The organic components contained in the kneaded material are organic substances containing C (carbon), and are, for example, polymeric compounds (thermoplastic resins) having thermoplasticity, oily compounds (wax, wax esters), etc. Specific examples of the organic components include polyolefins such as polyethylene, polypropylene, and ethylene-vinyl acetate copolymers, acrylic resins such as polymethyl methacrylate and polybutyl methacrylate, styrene resins such as polystyrene, polyesters such as polyvinyl chloride, polyvinylidene chloride, polyamide, polyethylene terephthalate, and polybutylene terephthalate, polyethers, polyvinyl alcohols, and copolymers thereof, as well as various resins such as various waxes, paraffins, higher fatty acids such as stearic acid, higher alcohols, higher fatty acid esters, and higher fatty acid amides. The organic components contained in the kneaded material can be one or more of the various organic components described above, which can be selectively mixed and used. The organic components contained in the kneaded material may be organic components contained in a binder, as in the case of general MIM. In this case, the binder may contain additives such as a plasticizer, an antioxidant, a degreasing accelerator, and a surfactant, in addition to the above-mentioned organic components, as necessary.

[0049] <Molded body production process> In the green body production process, the kneaded material produced in the kneaded material production process is injection molded to produce a green body. To produce the green body, an injection molding machine similar to that used in general MIM, equipped with a die with a cavity corresponding to the shape of the green body, can be used. The green body can be produced by injecting the kneaded material that has been appropriately plasticized by heating into the cavity of the die at an appropriate pressure, and cooling after holding the pressure for an appropriate period of time.

[0050] <Degreased body production process> In the degreased body preparation process, the green body prepared in the green body preparation process is used to remove the organic components constituting the green body to prepare a degreased body. As a method for removing the organic components from the green body, as in the general MIM, for example, a solvent degreasing method, a heat degreasing method, a combined degreasing method combining solvent degreasing and heat degreasing, etc. can be used as necessary. For example, according to the solvent degreasing method, the green body is immersed in a solvent that is soluble in the specific organic components contained in the green body, thereby dissolving and removing the specific organic components from the green body. For example, according to the heat degreasing method, the green body is heated to a temperature at which the organic components contained in the green body are thermally decomposed or higher (but below the temperature at which the mixed metal powder begins to sinter) and held for an appropriate period of time, thereby gasifying and removing the organic components from the green body through thermal decomposition.

[0051] For example, according to the combined degreasing method, a degreased body can be produced by dissolving specific organic components from a molded body by solvent degreasing to produce a precursor of the degreased body, and then gasifying and removing the organic components contained in the precursor by thermal degreasing. When producing a degreased body from a molded body containing oily waxes as organic components, it is preferable to select the combined degreasing method. According to the combined degreasing method, the waxes are dissolved by solvent degreasing to form voids inside the molded body (precursor of the degreased body), so that when the organic components remaining in the precursor are pyrolyzed and gasified by thermal degreasing, the gas can be quickly and sufficiently discharged from the precursor.

[0052] <Preparation of calcined body> The calcined body preparation step can be added after the above-mentioned degreased body preparation step and before the sintered body preparation step described later. In the calcined body preparation step, the degreased body is kept warm for a suitable period of time by the second heating at a temperature lower than the holding temperature in the first heating performed in the subsequent sintered body preparation step, and the metal powder constituting the degreased body is sintered so that the relative density does not exceed 90%, thereby producing a calcined body. For convenience, the sintering in the calcined body preparation step is called calcination. The calcined body can be produced by keeping the temperature at a temperature higher than the temperature at which the metal powder constituting the degreased body starts to sinter by the second heating, while keeping the temperature for a suitable period of time so that the relative density does not exceed 90%. Since the relative density of the calcined body does not exceed 90%, many voids exist inside. However, the calcined body is easier to handle than the degreased body in which the metal powder (particles) are not substantially bound to each other because the calcined body has slight mutual binding caused by the calcination. Furthermore, if organic components remain in the degreased body, the organic components remaining in the degreased body can be sufficiently pyrolyzed and removed by adding the calcined body production process and maintaining the temperature for an appropriate period of time through the second heating.

[0053] <Sintered body manufacturing process> In the sintered body preparation step, the degreased body prepared in the degreased body preparation step is used to sinter the metal powder constituting the degreased body by the first heating so that the relative density exceeds 90%, preferably sintering to a relative density of 95% or more to prepare a sintered body. When the above-mentioned calcined body preparation step is added, the calcined body prepared in the calcined body preparation step is used instead of the degreased body, and the metal powder constituting the calcined body is sintered by the first heating to prepare a sintered body. For convenience, the sintering in the sintered body preparation step is called the main sintering. The sintered body can be prepared by keeping the temperature at or above the temperature at which the sintering of the degreased body or the metal powder constituting the calcined body progresses by the first heating. The sintered body having a high relative density exceeding 90%, preferably a sintered body having a relative density of 95% or more, has few voids inside and has a dense sintered structure. In addition, by crushing the internal voids by the above-mentioned HIP treatment, it is also possible to obtain a sintered body having a higher relative density (for example, 98% or more) than the sintered body after the main sintering.

[0054] Next, the contents and results of experiments carried out for the purpose of confirming the effectiveness of the sintered body according to the present invention will be described.

[0055] In the experiments, as shown in Experiment Nos. 1 to 9 in Table 2, the above-mentioned Powder A was used as the standard metal powder, and the above-mentioned Powder B and Powder C were used as the mixed metal powder. Also, as described above, Powder B and Powder C used Powder S1 as the first metal powder and Powder S3 as the second metal powder. Also, in the experiments, metal powder made of an α+β type titanium alloy with a composition equivalent to Ti-6%Al-4%V (mass%) was used. Therefore, the material of all of Powder A, Powder S1, Powder S2, Powder B, and Powder C used in the experiments is an α+β type titanium alloy with a composition equivalent to Ti-6%Al-4%V (mass%).

[0056] Titanium (pure Ti), which is the base of α+β type titanium alloy, is more active and easily reacts with other elements than Fe (iron) and Ni (nickel), which are often used as the base of alloys. Titanium (pure Ti) also exhibits a hexagonal close-packed structure metal structure (α phase) at room temperature, and transforms at high temperatures (880℃ to 890℃) to exhibit a body-centered cubic lattice structure metal structure (β phase). By selectively adding elements such as Al, V, and Sn to titanium (pure Ti), an α+β type titanium alloy in which the β phase exists even at room temperature is obtained. When α+β type titanium alloy is appropriately kept at about 900℃ or higher, the α phase is easily transformed into the β phase, resulting in a large change in volume. It is thought that a degreased body (or calcined body) made of metal powder made of α+β type titanium alloy, which is easily active and easily undergoes a large change in volume due to transformation, is likely to undergo a large change in volume and become a sintered body with distorted shrinkage or distortion when appropriately kept at about 900℃ or higher. From this perspective, an α+β type titanium alloy was selected as a suitable material for confirming the effect of suppressing deformation of the sintered body during heating and sintering (main sintering). Specifically, a metal powder consisting of the well-known Ti-6%Al-4%V (by mass), known as 64 titanium, was used.

[0057] In the experiments, kneaded products of Experimental Nos. 1 to 9 shown in Table 2 were prepared in the kneaded product preparation step described above, and the above-mentioned green body preparation step, degreased body preparation step, calcined body preparation step, and sintered body preparation step were carried out to prepare sintered products of Experimental Nos. 1 to 9 shown in Table 3. The calcined body preparation step was added in order to sufficiently reduce the effect of organic components on shrinkage and deformation when the metal powder is heated and sintered (main sintering) in the sintered body preparation step.

[0058] In the experimental kneaded product preparation process, powder A (d50A is 25.4 μm) shown in Table 1 with a particle size (median diameter) of 45 μm or less was prepared with reference to Non-Patent Document 2 as a standard metal powder. In addition, powder S1 (d50P is 63.7 μm) and powder S2 (d50Q is 19.9 μm) shown in Table 1 were prepared as metal powders for preparing mixed metal powders. Next, powders S1 and S2 were used to prepare powders B and C shown in Table 2. Next, powders A, B and C were used to prepare kneaded products of Experiment Nos. 1 to 9 shown in Table 3. The mixing ratios (volume %) of powders A to C in the kneaded products of Experiment Nos. 1 to 9 are as shown in Table 3.

[0059] In the step of producing the green bodies in the experiments, the kneaded materials of the experiments Nos. 1 to 9 were injection molded to produce the green bodies of the experiments Nos. 1 to 9. The produced green bodies were rectangular flat plates having a length of 60 mm, a width of 10 mm, and a thickness of 2 mm.

[0060] In the degreased body preparation process of the experiment, the compacts of Experiment Nos. 1 to 9 were subjected to solvent degreasing to prepare the degreased bodies of Experiment Nos. 1 to 9. In order to thoroughly remove organic components from the degreased bodies after the solvent degreasing, a heat retention step equivalent to thermal degreasing was adopted in the subsequent calcined body preparation process.

[0061] In the calcined body preparation process of the experiment, the metal powders constituting the degreased bodies of Experiments 1 to 9 prepared in the degreased body preparation process were heated and sintered by the second heating at a lower temperature than the first heating in the subsequent sintered body preparation process to prepare calcined bodies. Note that since the degreased bodies were prepared by solvent degreasing, there is a possibility that organic components that were not dissolved in the solvent remain in the degreased bodies. Therefore, in the second heating to prepare the calcined bodies, a heating pattern was devised so that the organic components remaining in the degreased bodies are sufficiently removed before the metal powders constituting the degreased bodies start to sinter. Specifically, the second heating was a heating pattern in which a decompression step, a first heat retention step, a second heat retention step, a third heat retention step, and a cooling step were performed in this order.

[0062] In the first depressurization step of the second heating, the degreased body was supported by a refractory material and placed in a furnace at room temperature (about 25°C), and the inside of the furnace was replaced with argon gas, and then the pressure was reduced to about 133 Pa (about 1 torr). The refractory material was an alumina plate setter having an upper surface on which the degreased body having approximately the same shape as the molded body could be stably placed. The upper surface of the plate setter was covered with yttria powder. The reason why the refractory material was a plate setter was to suppress deformation (bending) in the thickness direction of the degreased body due to thermal contraction, and to make the deformation amount of the calcined body in the thickness direction approximately 0 mm. The reason why the upper surface of the alumina plate setter was covered with yttria powder was to suppress the metal powder constituting the degreased body from adhering to the plate setter.

[0063] In the first heat retention step of the second heating, the temperature inside the furnace was raised from room temperature (about 20°C) to the target temperature (about 400°C) and the temperature was maintained for about 2 hours. By this first heat retention step, organic components that melt or thermally decompose at about 400°C or lower are sufficiently removed from the degreased body.

[0064] In the second heat-retention step of the second heating, the temperature inside the furnace was further raised to the target temperature (about 650°C) and maintained at that temperature for about 2 hours. By this second heat-retention step, almost all of the organic components remaining in the degreased body were melted or thermally decomposed, resulting in a degreased body that is substantially free of organic components.

[0065] In the third heat-retention step of the second heating, the temperature inside the furnace was further raised to the target temperature (about 700°C) and kept at that temperature for about 3 hours. This third heat-retention step caused the metal powder constituting the degreased body to be slightly sintered, causing the metal powder (particles) to bond together to form a calcined body. Then, in the cooling step, the temperature inside the furnace was cooled to below the target temperature (about 45°C), and the calcined body was safely removed.

[0066] The sintered body preparation process performed following the above-mentioned calcined body preparation process in the experiment is a main sintering process in which the metal powder is sufficiently heated and sintered. In the sintered body preparation process in the experiment, the metal powder constituting the calcined bodies of Experiment Nos. 1 to 9 was sufficiently sintered by the first heating to prepare the sintered bodies of Experiment Nos. 1 to 9. In the first heating, the calcined body was supported by a refractory material and placed in a furnace at room temperature (about 25°C). The refractory material was an alumina flat plate setter having an upper surface on which both ends of the calcined body having approximately the same shape as the molded body can be placed and supported. The upper surface of the flat plate setter was covered with yttria powder. This allowed the calcined body to be supported at both ends with the central 25 mm in the length direction not touching the refractory material, and the deformation (deflection) of the calcined body in the thickness direction due to the sintering of the metal powder was made larger. The upper surface of the alumina flat plate setter was covered with yttria powder in order to prevent the metal powder constituting the calcined body from adhering to the flat plate setter.

[0067] In the first heating step of the sintered body production process, the inside of the furnace was replaced with argon gas, and then approximately 1×10 -3 The pressure was reduced to 1000 Pa, and the temperature was increased while maintaining the reduced pressure atmosphere as long as possible. The temperature was increased to about 1000°C for 3 hours, followed by about 1300°C for 4.5 hours. After reaching about 1300°C, the temperature was maintained for about 4 hours. After that, the temperature was cooled to about 1250°C for 3 hours, and the pressure inside the furnace was returned to atmospheric pressure before the sintered body was removed.

[0068] Through the above-mentioned steps, sintered bodies A to C of Experimental Nos. 1 to 9 shown in Table 3 were obtained. In Table 3, sintered bodies A of Experimental Nos. 1 to 3 are standard sintered bodies for comparison with the sintered bodies according to the present invention. Sintered bodies B of Experimental Nos. 4 to 6 and sintered bodies C of Experimental Nos. 7 to 9 are sintered bodies according to the present invention (examples of the present invention). As shown in Table 3, the sintered bodies of Experimental Nos. 1 to 9 have a density of 4.37 g / cm 3 ~4.59g / cm 3 Since the deviations are within the range of about 5%, it can be determined that the same degree of heating and sintering (main sintering) has been achieved for all sintered bodies.

[0069] [Table 3]

[0070] In order to evaluate the sintered bodies of Experimental Nos. 1 to 9 shown in Table 3, the deformation amount in the thickness direction of the sintered bodies (hereinafter referred to as "sintering deformation amount") was measured, and the measured value was used to determine the deformation ratio of the sintering deformation amount of the sintered bodies during heating and sintering (main sintering). Specifically, the sintering deformation amount of the sintered bodies of Experimental Nos. 1 to 9 was measured in the following procedure, and the measured value was used to determine the deformation ratio of the sintering deformation amount of the sintered bodies.

[0071] First, two flat supports are prepared and placed on a horizontal surface such as a surface plate. The two supports are placed so that the distance between them is 25 mm. Next, both ends of the sintered body in the length direction are placed on the upper flat surfaces of the two supports so that the deformation (warping) of the sintered body is downwardly convex. At that time, the sintered body is placed so that the approximate center of the length direction of the sintered body is located approximately in the center of the above-mentioned distance between them. Next, the sintered body is photographed from a direction perpendicular to the side surface along the length direction of the sintered body and parallel to the above-mentioned horizontal surface. At that time, a range (about 30 mm) including the above-mentioned 25 mm distance between them is photographed. Next, a perpendicular line is drawn to the convex part of the sintered body that is downwardly convex, based on the line connecting the corner edges (25 mm distance) of the upper flat surfaces of the two supports, and the maximum amount of the convexity is measured. In this invention, the maximum amount of the convexity measured by the above procedure is defined as the sintering deformation amount of the sintered body during heating and sintering (main sintering).

[0072] Next, the sintering deformation amount of the sintered body A (standard sintered body) of experiment number 1 measured by the above procedure was used as a comparison standard, and the sintering deformation amount of the sintered bodies of experiment numbers 1 to 9 was divided by the sintering deformation amount of the sintered body of experiment number 1 to obtain the deformation ratio of the sintering deformation amount of the sintered bodies of experiment numbers 1 to 9 as shown in Table 3. The deformation ratio of the sintering deformation amount (comparison standard) of the sintered body of experiment number 1 used as the comparison standard was 1.0. In addition, the average value of the deformation ratio of the sintering deformation amount of the sintered bodies was obtained for the standard sintered body A (experiment numbers 1 to 3), the sintered body B (experiment numbers 4 to 6) and the sintered body C (experiment numbers 7 to 9) of the present invention as shown in Table 3.

[0073] Fig. 6 is a graph showing the deformation ratio of the sintering deformation amount of the sintered bodies of Experiment Nos. 1 to 9 shown in Table 3, with the mixing ratio (volume %) of the powder in the kneaded products of Experiment Nos. 1 to 9 shown in Table 2 on the horizontal axis. Note that the lines (dotted lines) and curves (two-dot chain lines) shown in Fig. 6 are linear approximation lines and polynomial approximation (quadratic) curves obtained for each of the three symbols (●, ▲, ■).

[0074] Referring to Table 3, when the curved line (two-dot chain line) shown in FIG. 6 is observed, it can be seen that the deformation ratio of the sintering deformation amount of the sintered body A, which is a standard sintered body, fluctuates by about 0.23 (0.76 to 1.00) with respect to a fluctuation of about 5 volume % within the level of the powder mixing ratio in the kneaded material (about 65 volume % to about 70 volume %). Similarly, it can be seen that the sintered body B, which is an example of the present invention, fluctuates by about 0.05 (0.53 to 0.58). Similarly, it can be seen that the sintered body C, which is an example of the present invention, fluctuates by about 0.24 (0.16 to 0.29). From this, it was found that the deformation ratio of the sintering deformation amount of the sintered bodies A to C is suppressed to a relatively small fluctuation (about 0.24 or less) with respect to a fluctuation of about 5 volume % of the powder mixing ratio in the kneaded material.

[0075] Also, referring to Table 3, when the line segment (dotted line) shown in FIG. 6 is observed, it can be seen that the level (average) of the deformation ratio of the sintering deformation amount of the sintered body A, which is a standard sintered body, is about 0.89 with respect to the level (about 65 volume % to about 70 volume %) including a fluctuation of about 5 volume % of the powder mixing ratio in the kneaded product. Similarly, it can be seen that the level (average) of the sintered body B, which is an example of the present invention, is about 0.56, which is about 37% smaller than that of the sintered body A. Similarly, it can be seen that the level (average) of the sintered body C, which is an example of the present invention, is about 0.21, which is about 76% smaller than that of the sintered body A. From this, it was found that, from the viewpoint that the deformation ratio of the sintering deformation amount is suppressed to be small compared to the standard sintered body, for the sintered bodies B and C, the sintered body B is preferable, and the sintered body C is more preferable. In addition, considering the range of boundary conditions in the manufacturing experiment of the sintered body to which MIM is applied, it is considered that the mixing ratio of the powder in the kneaded product is preferably 60 volume % or more and 80 volume % or less.

[0076] FIG. 7 shows representative cross-sectional photographs of sintered bodies A to C. As shown in FIG. 7, the sintered structures of sintered bodies A to C are composed of multiple large crystal grains and many flat grains within each crystal grain. Furthermore, the many flat grains present in the sintered structures of sintered bodies A to C constitute the internal structure (lamellar structure) of each relatively large crystal grain. By looking at the cross-sectional photograph shown in FIG. 7, the difference in the sintered structures of sintered bodies A to C can be confirmed. However, the cross-sectional photograph shown in FIG. 7 alone cannot quantitatively show the difference in the sintered structures of sintered bodies A to C.

[0077] Therefore, in order to show the difference between the sintered structure of the standard sintered body (sintered body A) and the sintered structure of the present invention examples (sintered bodies B and C), that is, to differentiate between the sintered bodies A to C, it was decided to consider an appropriate index. Specifically, first, based on the image data of the cross sections of the sintered bodies A to C as shown in FIG. 7, d10 to d90 of the sintered bodies A to C shown in Table 3 were obtained. When obtaining d10 to d90 of the sintered bodies A to C, a measurement area (a square of 4 mm in length and width) was set in the image data of the cross section. Within the measurement area, the grain boundaries of the relatively large individual crystal grains were extracted without extracting the grain boundaries of the flat grains that constitute the internal structure (lamellar structure) of the relatively large individual crystal grains. The number and area (cross-sectional area) of the individual crystal grains separated by the extracted grain boundaries were obtained. In addition, the diameter of a circle having an area corresponding to the area of ​​each of the separated crystal grains was obtained, and this was taken as the grain size (circle equivalent diameter) of the crystal grain. In this way, the cumulative frequency of the number of crystal grains relative to the crystal grain size of sintered bodies A to C was obtained, and a cumulative frequency distribution curve (frequency distribution) was created, and d10 to d90 of sintered bodies A to C (experimental numbers 1 to 9) shown in Table 3 was obtained.

[0078] Table 4 summarizes the deformation ratio of the sintering deformation amount and the evaluation items based on the cumulative frequency (particle number) distribution curve of the crystal grain size for sintered body A (experiment numbers 1 to 3), sintered body B (experiment numbers 4 to 6), and sintered body C (experiment numbers 7 to 9) shown in Table 3. The deformation ratio of the sintering deformation amount is calculated by dividing the value (average) of the deformation ratio for sintering deformation shown in Table 3 by the value (average) of sintered body A, and converting it so that sintered body A is 1.0. In addition, the evaluation items based on the cumulative frequency (particle number) distribution curve of the crystal grain size are calculated by dividing the values ​​(average) of d10 to d90 shown in Table 3 for each sintered body A to C by d10, and converting it so that d10 is 1.0.

[0079] [Table 4]

[0080] FIG. 8 shows a graph of the experimental values ​​d10 / d10 to d90 / d10 shown in Table 4, with the horizontal axis representing the cumulative frequency of the number of crystal grains in the sintered body. As shown in Table 4 and FIG. 8, d10 to d90 are divided by d10 for each of sintered bodies A to C, and the cumulative frequency of the number of crystal grains in the sintered body is set to 0.1 as the starting point. This makes it easy to compare the transitions of d10 to d90 for sintered bodies A to C. The three curved segments shown by dotted lines in FIG. 8 are polynomial (quadratic) approximation lines for each of sintered bodies A to C. Looking at the three curved segments in FIG. 8, it can be seen that the curved segments for sintered bodies B and C tend to gradually move away from the curved segment for sintered body A as the cumulative frequency of the number of crystal grains in the sintered body increases. It can also be seen that in the region where the cumulative frequency of the crystal grain count of the sintered body is 0.4 to 0.8 (within the rectangular box shown by the two-dot chain line), the degree of separation of sintered body B and C from sintered body A becomes large. This shows that in the region where the cumulative frequency of the crystal grain count of the sintered body is 0.4 to 0.8, the difference between sintered body A, which is the standard sintered body, and sintered bodies B and C, which are examples of the present invention, is larger.

[0081] Therefore, we decided to study evaluation items to find appropriate indices for differentiating the standard sintered body (sintered body A) from the present invention examples (sintered bodies B and C) in terms of the deformation ratio of the sintering deformation amount of the sintered body in the cumulative frequency range of 0.4 to 0.8 in the frequency distribution of the crystal grain count of the sintered body (within the rectangular box shown by the two-dot chain line in Figure 8). Note that, in the study of evaluation items based on the frequency distribution, the experimental values ​​d10 to d90 of sintered bodies A to C shown in Table 3 were used.

[0082] Table 5 summarizes the deformation ratio of the sintering deformation amount of sintered bodies A to C and several evaluation items based on the frequency distribution of sintered bodies A to C. As shown in Table 5, with the decrease in the deformation ratio of the sintering deformation amount of sintered bodies A to C, d50 / (d90-d10) to d80 / (d90-d10) becomes smaller, and (d90-d50) / (d90-d10) to (d90-d80) / (d90-d10) becomes larger. Therefore, it is considered that d50 / (d90-d10) to d80 / (d90-d10) and (d90-d50) / (d90-d10) to (d90-d80) / (d90-d10) can be suitable indicators for differentiating sintered body A from sintered bodies B and C.

[0083] [Table 5]

[0084] Table 6 shows estimated values ​​of evaluation items relative to expected values ​​of deformation ratio of sintering deformation amount of sintered bodies based on the deformation ratio of sintering deformation amount and evaluation items of sintered bodies A to C shown in Table 5. The estimated values ​​of evaluation items of sintered bodies shown in Table 6 were calculated by setting expected values ​​of deformation ratio of sintering deformation amount of sintered bodies and using the following evaluation formula 1. <Evaluation formula 1> Es=Ea-(Da-Ds)×(Eb-Ec) / (Db-Dc) Where Es: Estimated value of evaluation item for sintered body Ds: Expected value (set value) of the deformation ratio of the sintering deformation amount of the sintered body Ea: Evaluation item of sintered body A (see Table 5) Da: Deformation ratio of sintering deformation of sintered body A (1.0) Eb: Evaluation items of sintered body B (see Table 5) Db: Deformation ratio of sintering deformation of sintered body B (0.63) Ec: Evaluation item of sintered body C (see Table 5) Dc: Deformation ratio of the sintering deformation of sintered body C (0.23)

[0085] [Table 6]

[0086] Based on Tables 5 and 6, the graphs shown in Figs. 9 and 10 were created with the expected value Ds (0.1 to 0.9) of the deformation ratio of the sintering deformation amount of the sintered body as the horizontal axis. The evaluation item Es of the sintered body shown in Fig. 9 is d40 / (d90-d10) to d80 / (d90-d10). The plot △ shown in Fig. 9 is the evaluation item of the sintered body B shown in Table 5. The evaluation item Es of the sintered body shown in Fig. 10 is (d90-d40) / (d90-d10) to (d90-d80) / (d90-d10). The plot □ shown in Fig. 10 is the evaluation item of the sintered body C shown in Table 5. From Fig. 9, it can be confirmed that the positions of the sintered bodies B and C (plots △ and □) are relatively close to two of the five line segments, d70 / (d90-d10) and d80 / (d90-d10). Similarly, when looking at Figure 10, it can be seen that, among the five line segments, the positions of sintered bodies B and C (plots △ and □) are relatively close to the (d90-d70) / (d90-d10) line segment.

[0087] Therefore, for sintered body B (deformation ratio of sintering deformation amount: 0.63) and sintered body C (deformation ratio of sintering deformation amount: 0.23), the error (%) of the evaluation items (estimated values) of sintered bodies B and C shown in Table 6 relative to the evaluation items (experimental values) of sintered bodies B and C shown in Table 5 was calculated as shown in Table 7. The error shown in Table 7 was calculated using the following evaluation formula 2. <Evaluation formula 2> Er=|1-Es / Ee|×100 Where Er: Error (%) Ee: Evaluation items (experimental values) of sintered bodies B and C shown in Table 5 Es: Evaluation items (estimated values) of sintered bodies B and C shown in Table 6

[0088] As shown in Table 7, the errors of d70 / (d90-d10) and d80 / (d90-d10) were less than 3% for both sintered bodies B and C. Similarly, the errors of (d90-d70) / (d90-d10) were less than 3% for both sintered bodies B and C. This makes it possible to numerically show that the positions of sintered bodies B and C (plots △ and □) are relatively close to the two lines of d70 / (d90-d10) and d80 / (d90-d10), as confirmed in Figure 9. Similarly, it makes it possible to numerically show that the positions of sintered bodies B and C (plots △ and □) are relatively close to the line of (d90-d70) / (d90-d10), as confirmed in Figure 10.

[0089] [Table 7]

[0090] A typical sintered body produced by MIM is a porous structure with a metal powder mixing ratio of about 60% to about 80% by volume that is transformed into a dense structure by heating and sintering, and is therefore relatively sensitive to fluctuations in manufacturing conditions. In the field of sintered bodies, which are sensitive to fluctuations in manufacturing conditions, if the error of the estimated value based on the experimental value is 3% or less, the estimated value is at a level that is sufficiently practical. Therefore, from the viewpoint that the error of the estimated value based on the experimental value is 3% or less, we decided to adopt d70 / (d90-d10), d80 / (d90-d10), and (d90-d70) / (d90-d10) from among the evaluation items based on the frequency distribution of sintered bodies, as indexes for evaluating whether the deformation ratio of the sintering deformation amount of the sintered body is suppressed to a small value.

[0091] Looking at Table 6, when the expected value of the deformation ratio of the sintering deformation amount of the sintered body is 0.8, the evaluation items of the sintered body, d80 / (d90-d10) are 1.20 and d70 / (d90-d10) are 1.03. Therefore, a sintered body whose integrated frequency distribution curve (frequency distribution) of crystal grain size satisfies d80 / (d90-d10)≦1.20 and d70 / (d90-d10)≦1.03 is highly likely to have a deformation ratio of the sintering deformation amount to the standard sintered body of 0.8 or less, and is therefore a sintered body (deformation-suppressed sintered body) in which distortion shrinkage and distortion during heating and sintering are suppressed to a small value.

[0092] Similarly, when the expected value of the deformation ratio of the sintering deformation of a sintered body is 0.8, the evaluation item of the sintered body, (d90-d70) / (d90-d10), is 0.35. Therefore, a sintered body whose integrated frequency distribution curve (frequency distribution) of crystal grain size satisfies (d90-d70) / (d90-d10)≧0.35 is highly likely to have a deformation ratio of the sintering deformation of the standard sintered body of 0.8 or less, and is therefore a sintered body (deformation-suppressed sintered body) in which distortion shrinkage and distortion during heating and sintering are suppressed to a small value.

[0093] In addition, when the expected value of the deformation ratio of the sintering deformation amount of a sintered body is 0.5, the evaluation items of the sintered body, d80 / (d90-d10) are 1.16 and d70 / (d90-d10) are 0.99. Therefore, a sintered body whose integrated frequency distribution curve (frequency distribution) of crystal grain size satisfies d80 / (d90-d10)≦1.16 and d70 / (d90-d10)≦0.99 is highly likely to have a deformation ratio of the sintering deformation amount of a standard sintered body of 0.5 or less, and is therefore a preferable sintered body (deformation-suppressed sintered body) in which distortion shrinkage and distortion during heating and sintering are suppressed to a smaller value.

[0094] Similarly, when the expected value of the deformation ratio of the sintering deformation amount of a sintered body is 0.5, the evaluation item of the sintered body, (d90-d70) / (d90-d10), is 0.39. Therefore, a sintered body whose integrated frequency distribution curve (frequency distribution) of crystal grain size satisfies (d90-d70) / (d90-d10)≧0.39 is highly likely to have a deformation ratio of the sintering deformation amount of a standard sintered body of 0.5 or less, and is therefore a preferable sintered body (deformation-suppressed sintered body) in which distortion shrinkage and distortion during heating and sintering are suppressed to a smaller value.

[0095] From the above, when the deformation ratio of the sintering deformation amount of the standard sintered body (sintered body A) during heating and sintering (main sintering) is taken as the comparison standard (1.0), the sintered body according to the present invention (sintered bodies B and C) is sufficiently small in the deformation ratio of the sintering deformation amount. In addition, the effectiveness of the present invention was confirmed from the viewpoint that d80 / (d90-d10), d70 / (d90-d10) and (d90-d70) / (d90-d10) based on the cumulative frequency distribution curve (frequency distribution) of the crystal grain size of the sintered body were found as appropriate indicators for differentiating the standard sintered body (sintered body A) from the sintered bodies according to the present invention (sintered bodies B and C), and the appropriate ranges of each were determined. Therefore, the sintered body according to the present invention can be a practical means for providing a sintered body (sintered body with suppressed sintering deformation) in which distortion shrinkage and distortion deformation during heating and sintering are suppressed to a small extent, which can be mass-produced by a simple means using MIM.

Claims

1. A sintered body, in which, when the 10% crystal grain size in a cumulative frequency distribution curve of crystal grain size is d10, the 70% crystal grain size is d70, the 80% crystal grain size is d80, and the 90% crystal grain size is d90, the cumulative frequency distribution curve satisfies d80 / (d90-d10)≦1.20 and d70 / (d90-d10)≦1.

03.

2. 2. The sintered body according to claim 1, wherein the cumulative frequency distribution curve satisfies (d90-d70) / (d90-d10)≧0.35, where d60 is the crystal grain size at 60% frequency in the cumulative frequency distribution curve.

3. The sintered body according to claim 1, wherein the cumulative frequency distribution curve satisfies d80 / (d90-d10)≦1.16 and d70 / (d90-d10)≦0.

99.

4. The sintered body according to claim 2, wherein the cumulative frequency distribution curve satisfies (d90-d70) / (d90-d10)≧0.

39.

5. 3. The sintered body according to claim 1, which is made of an α+β type titanium alloy.

Citation Information

Patent Citations

  • Metal powder injection molding method and binder used therefor

    JP2001152205A

  • Powder metal injection molding compound, metal powder molding, manufacturing method for sintered body, and sintered body

    JP2018145481A